Application of telemedicine technology for cardiovascular diseases management during the COVID-19 pandemic: a scoping review - Asadi, Hassan; Toni, Esmaeel; Ayatollahi, Haleh (Frontiers in Cardiovascular Medicine, 2024)
Background: Recently, the use of telemedicine technology has increased due to the Covid-19 pandemic. Cardiovascular diseases management is one of the areas that has benefited from using this technology. This study aimed to identify the applications of telemedicine for cardiovascular diseases management during the Covid-19 pandemic.Methods: This scoping study was conducted in 2023. Various databases, including PubMed, Web of Science, Scopus, the Cochrane Library, Ovid, CINAHL, ProQuest, and IEEE Xplore along with Google Scholar were searched and all related quantitative, qualitative, and mixedmethod studies published in English between 2020 and 2022 were included. Finally, the required data were extracted, and the findings were reported narratively.Results: A total of 17 articles were included in this study. The results showed that teleconsultation via telephone and videoconferencing were the most common used technologies. Telemedicine helped to improve clinical impacts such as patient health status and quality of care, and reduced hospitalizations and re-admission rates compared to in-person visits. The non-clinical impact included reducing waiting time, in-person visits, and healthcare costs during the Covid-19 pandemic.The Covid-19 pandemic has led to an increased use of telemedicine technology, especially for patients with cardiovascular diseases. As teleconsultation and telemonitoring are useful for cardiovascular diseases management and regular examinations, future research should investigate how these technologies can be improved and used for a wider population.